TINDAK TUTUR DIREKTIF PEDAGANG SAYUR-MAYUR DI PASAR ALAHAN PANJANG KABUPATEN SOLOK - Maryunis, Maryunis; Amir, Amril; Tressyalina, Tressyalina (Jurnal Bahasa dan Sastra, 2012)
This research is done to describe the pattern and the function of Speech  Act Directive Trader Vegetable in Market Alahan Panjang Kabupaten Solok. This research is also done to describe the situation of greengrocers’ speech in the market of Alahan panjang, the Regency of Solok. Data is collected by using observation technique that used tape recorder as recording instrument. Subject in this research is the greengrocers in the market of Alahan Panjang, the Regency of Solok. However, outcome of this research are the pattern, the function, and the situation of 194 greengrocers’ speeches in the market of Alahan panjang, the Regency of Solok.   Kata kunci: Tindak Tutur, Direktif, Pedagang,